Analysis Docking Of Plasmodium Falciparum Enoyl Acyl Carrier Protein Reductase (Pfenr) With Organic Compunds From Virtual Screening Of Herbal Database - Nya Daniaty Malau; St Fatimah Azzahra (Chemistry Education Program, the University of Mataram, 2020)
Malaria is one of problematic infectious diseases worldwide. The absence of an effective vaccine and the spread of drug resistant strains of Plasmodium clearly indicate the necessity for the deveploment of new chemotherapeutic agents. Recent method being developed is searching a new drug of antimalarial using in silico screening, or also known as virtual screening. One of enzyme target that important for growth of the malaria parasite is Plasmodium falciparum Enoyl Acyl Carrier Protein Reductase (PfENR). Inhibition of this enzyme cause the fatty acid biosynthesis type II will be terminated. In this research, in silico screening was performed using AUTODOCK VINA software to find inhibitor candidates of PfENR by using ligands from the database of Medicinal Plants in Indonesia. On the AUTODOCK VINA software moleculer docking experiments were performed between ligands and macromolecule target PfENR. This target that has been optimized with residue removal and charges addition. Ligand is expected to be the PfENR inhibitors.